Social Practices (Reform) Act, 2033 (1976) of Nepal in light of Jurisprudence - Lamichhane, Bimal Prasad; Baral, Sagar (Janaprakash Journal of Multidisciplinary Research, 2023)
The paper delves and critically analyze the concept of Volksgeist in Nepali society concerning the Social Practices (Reform) Act, 2033 (1976) and conducts a comparative analysis with the proposed draft bill, tracing the evolving Volksgeist. Ultimately, the paper concludes that jurisprudentially, laws can be categorized as either obeyed or transgressed, with Savigny’s Volksgeist doctrines providing insight into the reasons for transgressions. It advocates for a self-realization approach in addressing social matters, aligning with Volksgeists perspective of law as a biological and evolutionary phenomenon.